Implementation of Arabic-Based Audio Visual Media in Learning Listening Skills - Prasetya, Panji; Al Anshory, Abdul Muntaqim; Hasaniyah, Nur; Putri, Noviantika Luksiana (Journal of Arabic Language Teaching, 2024)
Arabic language learning in school institutions often challenges the development of basic skills, especially listening skills. This study aims to describe the implementation process of audio-visual media in Arabic language learning, especially listening skills, in grade 3 of MIN 1 Madiun City. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research subjects were Arabic teachers and 3rd-grade students of MIN 1 Madiun City. The results showed three stages in the application of audio-visual media: the preparation, implementation, and follow-up. The teacher designs and prepares the materials and audio-visual devices in the preparation stage. The implementation stage involves using audio-visual media during the learning process in the classroom. In the follow-up stage, teachers conduct evaluations and provide feedback to students. With audio-visual media, students can understand the material taught better, creating a more conducive and enjoyable learning atmosphere. In conclusion, audio-visual media effectively improves students' listening skills in learning Arabic at MIN 1 Madiun City.